2020
DOI: 10.1111/jocd.13876
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy evaluation of Endolift‐based Subcision on acne scar treatment

Abstract: Background People with acne scar suffer from destruction to the surface of the skin. Treating acne scars is a challenge that might need several methods. Aims Subsection is a method that has been informed to be a useful method in treating rolling acne scars. While Subcision is a valued procedure, its effect is mild to moderate due to its high reappearance rate, and patients' dissatisfaction with some of the side effects such as inflammation after procedure. Patients/Methods In this pilot study, 9 rolling acne s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 11 publications
5
31
0
6
Order By: Relevance
“…Also, brow ptosis is informed frequency after horizontal forehead lines BTXA treatment 18 . Endolift laser as a non‐invasive method is desirable for treatment of the skin disorder, and recently, it has been very popular 19,20 . In this study, we used Endolift laser for treatment of deep wrinkles on the upper face and frown line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, brow ptosis is informed frequency after horizontal forehead lines BTXA treatment 18 . Endolift laser as a non‐invasive method is desirable for treatment of the skin disorder, and recently, it has been very popular 19,20 . In this study, we used Endolift laser for treatment of deep wrinkles on the upper face and frown line.…”
Section: Discussionmentioning
confidence: 99%
“…18 Endolift laser as a non-invasive method is desirable for treatment of the skin disorder, and recently, it has been very popular. 19,20…”
Section: Discussionmentioning
confidence: 99%
“…The study showed a 90% improvement. The number of lesions before the treatment was 25.5 ± 12.1, and after treatment, it was reduced to 11.4 ± 2.1 ( p < 0.05) [ 65 ].…”
Section: Methods Of Acne Scars Managementmentioning
confidence: 99%
“…In one very innovative study, Nilforoushzadeh et al used a 300-micron laser fiber to perform energy- and wire-based subcision, noting 100% improvement according to clinical photographic data evaluation. 59 The authors noted that inflammation and postoperative erythema were less severe than what is usually observed with cannula-based subcision and lasers. 59 …”
Section: Subcisionmentioning
confidence: 97%
“… 59 The authors noted that inflammation and postoperative erythema were less severe than what is usually observed with cannula-based subcision and lasers. 59 …”
Section: Subcisionmentioning
confidence: 97%